2022
DOI: 10.1001/jamadermatol.2021.5390
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Characteristics, Disease Course, and Outcomes of Patients With Acute Generalized Exanthematous Pustulosis in the US

Abstract: IMPORTANCEAcute generalized exanthematous pustulosis (AGEP) is a rare, severe cutaneous adverse reaction associated with systemic complications. Currently available data are largely limited to small retrospective case series.OBJECTIVE To describe the clinical characteristics, disease course, and outcomes of a heterogeneous group of patients with AGEP across the US. DESIGN, SETTING, AND PARTICIPANTSA retrospective review of a case series of patients was conducted from January 1, 2000, through July 31, 2020. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 23 publications
2
34
1
1
Order By: Relevance
“…As for the timeline, the implication of gemcitabine seems more likely than nivolumab. Creadore et al 6 found a median time from medication initiation to AGEP occurrence of 3 days (IQR, 1–9) in a large, retrospective, population of patients ( n = 340). Furthermore, AGEP induced by gemcitabine has already been reported 7 with an interval of four days between gemcitabine infusion and onset of AGEP.…”
Section: Discussionmentioning
confidence: 99%
“…As for the timeline, the implication of gemcitabine seems more likely than nivolumab. Creadore et al 6 found a median time from medication initiation to AGEP occurrence of 3 days (IQR, 1–9) in a large, retrospective, population of patients ( n = 340). Furthermore, AGEP induced by gemcitabine has already been reported 7 with an interval of four days between gemcitabine infusion and onset of AGEP.…”
Section: Discussionmentioning
confidence: 99%
“…AGEP is distinguished from DRESS syndrome by its nonfollicular small pustules surrounded by edema and erythema [ 5 , 15 ]. This, coupled with epidermal acanthosis, spongiosis, and microvesicle and pustule formation on biopsy, makes the diagnosis [ 5 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…AGEP is distinguished from DRESS syndrome by its nonfollicular small pustules surrounded by edema and erythema [ 5 , 15 ]. This, coupled with epidermal acanthosis, spongiosis, and microvesicle and pustule formation on biopsy, makes the diagnosis [ 5 , 15 ]. Immunophenotypical features identify DRESS syndrome: cutaneous effector lymphocytes represent a large quantity of the polyclonal CD8 + granzyme B + T lymphocytes [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations